VARIATIONS IN THE USE OF MAKE A MATCH LEARNING MODELS, SCRAMBLE LEARNING MODELS, AND CONVENTIONAL LEARNING MODELS TO IMPROVE STUDENT LEARNING OUTCOMES - Carolina Selfisina Ayal; Binti Rohmawati; Taufan Talib (Science Map Journal, 2022)
Variations in the use of various mathematical learning models are expected to provide an overview of the ability of students to understand mathematical concepts. This study aimed to determine the variation of students' mathematics learning outcomes by using the make a match learning model, the scramble learning model, and the Conventional learning model. Using the quasi-experimental method, the make a match and scramble learning model was applied as the independent variable and the conventional learning model as the control variable. Statistically, the F test was used to show that there was a difference in the mean with the value of Fcount = 4.22 > Ftable = 3.18, and Tukey's HSD analysis showed a value of 14.18 and compared to the group mean, it was concluded that the use of the make a match learning model gave the better learning result value between scramble and conventional learning models